Pengaruh Pemberian Ekstrak Etanol Daun Kecapi (Sandoricum koetjape (Burm.f.) Merr.) Terhadap Penurunan Kadar Kolesterol Total pada Mencit Jantan (Mus musculus) - Rudi Kartika (JURNAL KIMIA MULAWARMAN, 2016)
The research about utilization of ethanol extract form leafkecapi (Sandoricum koetjape (Burm.f.)Merr.)has been done, it proved could decrease  total cholesterol levels in male mice (Mus musculus). In this research sample macerated with ethanol 96% and then concentrated by rotary evaporator, and gained 15.6% of yield. Based on the results of phytochemical test, secondary metabolites compound that contained in bark kecapi are alkaloid, flavonoid, triterpenoid, steroid, phenolic and saponin. On antihiperkolesterolemia activity test by using male mice, there are several treatments that negative control (-), positive control (+) and three treatment with different doses i.e. a low doses (9.5 mg/kg BB), middle doses (19 mg/kg BB) and high doses (38 mg/kg BB). The parameter measured was blood serum of male mice by using a Cholesterol Test Strips. From this test it showed that the effectiveness of decreased total cholesterol level doses of 19 mg/kg BB showed total cholesterol level under 100 mg/dL. Keywords:      Leaf kecapi (Sandoricum koetjape (Burm.f.) Merr.), Phytochemicals test, Total cholesterol levels, Cholesterol test strips.